Peningkatan Kompetensi Guru Sekolah Dasar dalam Menghadapi Era Digital melalui Pelatihan Gamifikasi Wordwall dan ChatGPT - Arifin, M. Zainal; S, Deddy Sofyan; Gani, Resyi A; Windiyani, Tustiyana; Kulsum, Siti; Putri Yusup, Muthia Khairunnisa (Universitas Pahlawan Tuanku Tambusai, 2025)
The use of gadgets among primary school students is increasingly common in the digital era, but at SDN Gang Aut in Bogor City and surrounding areas, their utilisation in learning is still minimal. Most teachers use simple learning media, while only a few students utilise gadgets as learning aids at home. This suggests the need to adopt more varied and internet-based learning methods to fulfil students' diverse learning needs. Internet-based learning can provide access to extensive educational resources and encourage active student participation. One effective method is gamification, which integrates game elements to increase student motivation and engagement. However, a challenge faced is the lack of teachers‘ understanding and skills in using digital media, such as Wordwall and ChatGPT applications. To address this issue, a six-month community service programme (PKM) is planned that aims to improve teachers’ competencies through gamification training. The programme will include the provision of materials, practice using digital tools, and evaluation through pre-tests and post-tests. By improving teachers‘ skills in integrating technology, it is expected that students’ use of gadgets will be more effective in supporting learning in the digital era.